Emotional intelligence in undergraduate students of a private university in Metropolitan Lima - Rosario Quiroz, Fernando Joel (2014)
The research aimed to establish the differences in the emotional intelligence of students in the first cycle of a private university. The Bar-On Emotional Quotient Inventory was applied to a sample consisting of 1,940 male and female subjects from 16 to 25 years old. Crossover design was used with a significance level of 0.05 (p <0.05) and found no statistically significant difference regarding sex between the following components: interpersonal component, stress management and general mood. There are differences regarding the type of school in total emotional quotient, intrapersonal component, adaptability, stress management, the subcomponents of self-knowledge, assertiveness, self-concept, self-realization, social responsibility, problem solving, reality testing, flexibility, stress management, impulse control and optimism.